Detection of Lithium Plating During Thermally Transient Charging of Li-Ion Batteries - Carter, Rachel; Klein, Emily J.; Kingston, Todd A.; Love, Corey T. (Frontiers in Energy Research, 2019)
Li-ion batteries are prone to thermal transients imposed by external environmental conditions and/or operationally-induced self-heating characteristics. The material properties, form factor, and implemented cooling strategy of a battery influence the severity and behavior of thermal transients. In contrast to equilibrated low temperatures (0˚C), both substantial and mild (40 to 0˚C and 10 to 0˚C) temporally transient thermal conditions, result in approximately half of the Li+ ions plate as lithium metal at the anode, as opposed to intercalating, in the first charge. This quantity of plated lithium accelerates capacity loss in subsequent cycles and causes rapid onset of jellyroll collapse (cycles 5-8). The plating process induced by charging under a thermal transient causes a unique drop in voltage during charging, resulting in a negative differential voltage, which is not observed in subsequent cycles when the cell temperature has reached thermal equilibrium or in any equilibrium condition. Because a negative differential voltage is distinct, it provides route for detection to prevent rapid degradation and compromised safety. Accelerated rate calorimetry assesses cell safety after substantial plating and jellyroll collapse induced by charging under a temporally thermal transient condition. Self-heating begins at temperatures as low as 35˚C and can wall rupture provides risk of propagation failures in battery packs. Charging during thermal transients is identified as a plating-prone condition that alters the long-term performance and safety of Li-ion batteries. This work exemplifies the importance of understanding the role of thermal transients in pack assemblies to enable safe operation.